Gambaran Penjualan Vitamin Pada Masa Pandemi Covid-19 di Kabupaten Bangkalan - Firmaniar, Rizdyana; Retnaningtyas, Yayuk (Jurnal Indonesia Sehat, 2023)
Background:  The COVID-19 pandemic in 2021 is a major case where in January 2021 there was one of the highest peaks of positive cases. The virus can infect humans through airborne or droplet transmission. In that year there was also an increase in deaths due to COVID-19 infection. Therapeutic management for this disease requires antiviral drugs and vitamins. The purpose of this study is to determine the description of vitamin sales during the covid-19 pandemic. Method:  This study uses a quantitative descriptive method with retrospective data collection. The sales data taken is data that occurred on January 1 - December 31, 2021 at Pharmacy "X". Result:  there are 61 types of vitamins sold.  There are 2 types of dosage forms used, namely tablets and syrups. For tablet dosage forms there are 44 types and for syrup dosage forms there are 18 types. The percentage of sales results for syrup and tablet dosage forms has almost the same results. in the first quarter was the highest vitamin sales phase at 30.74%, then continued in quarter 2 at 28%. In the third quarter there was a decrease in sales, namely 18.69% and in the fourth quarter there was an increase in vitamin sales but not as high as in quarter one (21.60%). Conclusion:  Sales of vitamins in the form of tablets and syrups during the 2021 pandemic have a similar picture, there is the highest increase in the first quarter,  which is in tablet preparations of 30.74% and 30.56% for syrup. The lowest result was in the third quarter are 18.69% for tablet preparations and 18.50% for syrup.